2018
DOI: 10.1016/j.socscimed.2018.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness in middle age and biomarkers of systemic inflammation: Findings from Midlife in the United States

Abstract: Feeling lonely is associated with systemic inflammation in middle-aged community-dwelling US adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
52
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(58 citation statements)
references
References 77 publications
3
52
1
Order By: Relevance
“…Similarly, for fibrinogen, some (Mezuk et al, ; Nersesian et al, ) but not all studies (Shankar et al, ) have detected an association between loneliness and raised fibrinogen concentrations. One recent study of 927 adults detected an association between loneliness and raised circulating interleukin‐6 (IL‐6) concentrations (Nersesian et al, ).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Similarly, for fibrinogen, some (Mezuk et al, ; Nersesian et al, ) but not all studies (Shankar et al, ) have detected an association between loneliness and raised fibrinogen concentrations. One recent study of 927 adults detected an association between loneliness and raised circulating interleukin‐6 (IL‐6) concentrations (Nersesian et al, ).…”
Section: Introductionmentioning
confidence: 95%
“…Loneliness has been linked with upregulation of proinflammatory gene expression (Cole, Hawkley, Arevalo, & Cacioppo, 2011), but associations with circulating inflammatory markers have been mixed. Some studies have found increased circulating C-reactive protein (CRP) levels (Cole et al, 2007;Nersesian et al, 2018), whereas others have found no association (McDade, Hawkley, & Cacioppo, 2006;Mezuk et al, 2016;Shankar, McMunn, Banks, & Steptoe, 2011). Similarly, for fibrinogen, some (Mezuk et al, 2016;Nersesian et al, 2018) but not all studies (Shankar et al, 2011) have detected an association between loneliness and raised fibrinogen concentrations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caring and respect in social relationships prompts a sense of well-being-together they act as a buffer against health problems (4) and catalyze myriad health bene ts. Loneliness is a perceived lack in quality or quantity of one's relationships (5) and predicts various health outcomes, including; systemic in ammation, increased blood pressure, depression, weight gain, smoking alcohol/drug use, and alone time (6)(7)(8)(9)(10). Loneliness is also closely linked with accelerated loss of physical functioning and health with age, and an increased likelihood that an older person discontinues PA over time (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…First, there appear to be direct links between isolation or loneliness and activation of systemic biological processes that increase risk of cardiovascular disease such as raised concentration of inflammatory biomarkers and disruption of adrenocortical rhythms. 10 A second set of potential mechanisms relate to lifestyle and other behaviours. Social isolation is associated with less physical activity, poorer diet and more smoking over periods up to 10 years in older people.…”
mentioning
confidence: 99%